Health care in Uganda : Selected issues - Hutchinson, Paul; Habte, Demissie; Mulusa Mary. (Washington, D.C. : World Bank, 1999)
This technical paper summarizes the results of three research efforts concerning current health care issues in Uganda. Its purpose is to summarize key actions and identify new challenges. In Part I, 'Equity of Access to Health Services in Uganda: The Effects of Income, Gender, Proximity to Services, and Quality of Care', the author examines a number of factors that affect access to health services, including quality of services and income. Part II of this technical paper, 'Decentralization of Health Services in Uganda: Moving Toward Improved Delivery of Services', summarizes the key actions that have been undertaken during the decentralization of Uganda's health sector and identifies challenges that are emerging during this process. Part III, 'Malaria: A Priority Health Problem', summarizes the status of malaria control in Uganda and highlights some of the key issues that need to be addressed to further strengthen malaria control efforts.
Includes bibliographical references and index.
osa 18/08/2016
Ref
Keywords: Medical care - Uganda; Public health care - Uganda; Malaria -Uganda.; Uganda